Towards New Fiscal Rules in the Euro Area? - Catherine Mathieu; Henri Sterdyniak (Intereconomics, 2022)
Faced with the impossibility of reaching a political agreement to review the fiscal treaties, the Commission could limit itself to applying the current rules with flexibility, which would maintain an ambiguous situation: much ado about nothing.
Keywords: E62; H63; H77; 330; Finanzpolitik; Öffentliche Schulden; EU-Staaten